Perceived Effective Entrepreneurship Education and Entrepreneurial Intention: The Role of the Perception of University Support and Perceived Creativity Disposition - Keat, Yeng; ., Nasiru (Journal of Education and Vocational Research, 2015)
In order to increase our understanding of the factors that underlie entrepreneurial intention formation, this article investigates the roles of individual creativity disposition and the perception of university support. The study considers how the personal characteristic may mediate students’ perception of effectiveness of entrepreneurship education and entrepreneurial intention. The study also aims to determine the perception of university support that could moderate the relationship between perception of the effectiveness of entrepreneurship education and creativity disposition. Using a survey of 158 university students and employing Structural Equation Modelling (SEM) with AMOS version 22, the results show that perceived creativity disposition facilitate our understanding on the entrepreneurship education and entrepreneurial intention relationship. However, in our analysis, university support does not invigorate the role of entrepreneurship education in enhancing perceived creativity disposition. Implications for research and practice are provided.